Peran United Nation Environment Programme (UNEP) Sebagai Lembaga Lingkungan Hidup Internasional dalam Pengelolaan Lingkungan Hidup - Kamila Insani (LPPM Universitas Ekasakti Padang, 2023)
This research aims to examine the role and position of international environmental institutions in environmental management. Environmental issues are international issues because they have broad effects, concerning the exploitation of global resources such as oceans and the atmosphere, as well as transnational environmental destruction. The United Nations Environment Programme (UNEP) is an environmental agency of the United Nations (UN) that specifically deals with global environmental issues by actively voicing the enforcement of sustainable development in the world. The research method used in this paper is descriptive analysis method with historical approach and conceptual approach. The results of this study indicate that the UN through UNEP is able to suppress government policies in cooperation activities for the achievement of global environmental protection programs.